SUBJECT OF UNLAWFUL ISSUANCE OR USE OF AN OFFICIAL DOCUMENT CERTIFYING COMPLIANCE WITH GOODS, SERVICES OR WORKS BY SAFETY REQUIREMENTS - L. A. Kamaliyeva (Russian Journal of Economics and Law)
The article analyzes the point of view of scientists on the subject of a special definition of the crime and its symptoms. Defined the subject of unlawful issuance or use of the official document, falsely certifying compliance with the goods, works or services, safety of life or health of the consumer, options offered training activities of perpetrators.